Perlindungan dan Kedudukan Hukum Anak Diluar Kawin Perspektif Undang-Undang No. 35 Tahun 2014 Tentang Perlindungan Anak - Mahfud, Mahfud; Hardyansah, Rommy; Mujito, Mujito; Saktiawan, Pratolo (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Children are entrusted as well as gifts from God who are obliged to receive affection in their proper growth and development, regardless of their parents' backgrounds. However, in real life, there are some children who are born out of a legal marriage (registered by the state), this is often the target of discriminatory treatment, both from a social and legal perspective. This research aims to explore in depth the form of protection and legal status of children outside marriage based on the perspective of Law No. 35 of 2014 concerning Child Protection. This research is a normative research with a legal approach and theories that are relevant to the research problem, and the results of the study show that according to the laws and regulations regarding the guarantee of every child to obtain legal protection and recognition, at the practical level there are still legal vacancies, especially related to the recognition of the civil status of children outside of marriage, such as inheritance rights and legal relations with biological fathers. For this reason, collaboration between the legal apparatus, state institutions, and the collective consciousness of the community is needed to ensure the fulfillment of children's rights in a fair and free manner from discrimination.